2019
DOI: 10.13057/biodiv/d201123
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Analysis of weed vegetation in immature and mature oil palm plantations

Abstract: Abstract. Satriawan H, Fuady Z. 2019. Analysis of weed vegetation in immature and mature oil palm plantations. Biodiversitas 20: 3292-3298. The species of weeds which grow and dominate in palm oil areas depend on location, local climate, and the light received. This research aimed to determine the diversity of weeds in the planting of palm oil with a different age grown in 2012, 2013, 2014 and 2016. The sample slots measured uniformly at 1 m x 1 m totaling 25 plots. Vegetation analysis was conducted to the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…In general, oil palm plantations have nuisance plants called weeds. Satriawan and Fuady (2019) stated that the most common weed species found in oil palm plantations is Asystasia intrusa. The weeds belong to the same family as Asystasia gangetica (L.) T. Anderson.…”
Section: Introductionmentioning
confidence: 99%
“…In general, oil palm plantations have nuisance plants called weeds. Satriawan and Fuady (2019) stated that the most common weed species found in oil palm plantations is Asystasia intrusa. The weeds belong to the same family as Asystasia gangetica (L.) T. Anderson.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the molecular data and the mathematical analysis showed that there was no significant difference in plant diversity in the D. metesae diet between the GAP and non-GAP plantations (Figure 5), even though the agricultural practices differed significantly between the two in terms of chemical application (Saswattecha et al, 2015), which would have had very significant impacts on the diversity of weeds and the associated biota (Darras et al, 2019). This might be because in our study, the weed species commonly found in the oil palm plantations such as A. gangetica, Clidemia hirta and Drymaria cordata (Ali et al, 2021;Satriawan and Fuady, 2019) could not be traced or detected in the diet of D. metesae (Figure 2). However, A. gangetica had been documented in other studies as having an important role in the abundance of parasitoids other than D. metesae (Wood and Norman, 2019a).…”
Section: P R E S Smentioning
confidence: 74%
“…Analysis of vegetation composition and diversity followed Tjitrosoedirdjo et al (1984) and Satriawan & Fuady (2019). The community composition of understorey vegetation that grows on oil palm plantations was analyzed using Important Value Index (IVI) and calculated as follow:…”
Section: Vegetation Analysismentioning
confidence: 99%